Implementação de metodologias LEAN para a melhoria da eficiência operacional da produção de Molas Técnicas - Sá, Renato Silva de (2022)
With given proves the Lean methodology still shows as a extremely valuable tool for top managements of production company´s. Scherdel Group is no exception do this general rule, with several factory´s of the group having implemented lean tools to help them, it comes the time to try and implement in Portugal. The objectif of this dissertation is to be able to elaborate an action plan and study the best way to apply this methodology to the current reality. This investigation was done using several known tools from lean that are known to general public such as : VSM- Value stream maping , Heijunka, PDCA, which with the assistance of the top management of the unit and members of Scherdel LEAN team were used to identify the best practices which will helps us improve the factory unit. After evaluating some mesure such as the VSM in which we obtain the information that if applied the Technic of Heijunka so that we could create a balanced planning that would allow us to improve the follow of the production step – grinding. In conclusion, even though it was identified a possible solution with theorical results, it has been noted that is necessary a visual implementation of this tool working in another plant so visualize the results before advancing with field tests.